Evaluation of the effectiveness of technological advances in health education - Cedeno Caballero, Jim Victor; Vega Velasquez, Maricela Isabel; Reyes Galarza, Isabel Victoria; Palma Reyes, Jeremy Jorge (Universidad Ciencia y Tecnología, 2022)
The following research work reflects the study of the relationship and influence, besides the efficacy, that exists between the aspects of the arrangement and management of higher education in Health Sciences area and the Information and Communication Technologies (ICTs). A bibliographic review was carried out with criteria based on the observation to recognize the technological aspects that have eased health education area. The main results show that health education has been greatly favored with the use of technological tools due to their convenience about time and space, since user can access information and education whenever and wherever they wish to.